2021
DOI: 10.1021/acssuschemeng.0c07889
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an Environmentally Friendly Water-Soluble Luminous Material with Interstitial Site Occupancy

Abstract: As an essential precursor, K2MnF6 plays an important role in the preparation of Mn4+-activated fluoride materials, but its deterioration in pure water hampers development of a green route. Herein, we report a simple and high-speed synthetic route to obtain an environmentally friendly water-soluble KHF2:Mn4+ luminous material by engineering the interstitial Mn4+ site, which is confirmed by combining with DFT, XRD Rietveld refinement data, solid-state NMR, Raman spectrum, and TG/DSC curves. Meanwhile, KHF2:Mn4+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…In recent years, WLEDs (white light-emitting diodes) with stable performance, energy saving, and outstanding luminescent characteristics have increasingly become an important requirement in the display and lighting elds. [1][2][3][4][5] At the moment, the commercially available WLEDs are composed of yellow emitting phosphors and blue emitting chips. 6 Although the device can produce white light, due to the lack of a red light component, its corresponding disadvantages are low color rendering index (R a < 80) and high color temperature (CCT > 4500 K).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, WLEDs (white light-emitting diodes) with stable performance, energy saving, and outstanding luminescent characteristics have increasingly become an important requirement in the display and lighting elds. [1][2][3][4][5] At the moment, the commercially available WLEDs are composed of yellow emitting phosphors and blue emitting chips. 6 Although the device can produce white light, due to the lack of a red light component, its corresponding disadvantages are low color rendering index (R a < 80) and high color temperature (CCT > 4500 K).…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H NMR spectrum of KSFM shows two signals at 1.39 and 6.08 ppm. The broad peak at 6.08 ppm corresponds to the O–H–O band of adsorbed water from the air atmosphere, while the peak at 1.39 is due to the interaction of proton nuclei from the atmosphere with the fluorine of KSFM . As for KSFM@OAm, there are five peaks as follows: a broad peak at 1.42 ppm for the methylene group (−CH 2 −), a peak at 1.01 ppm for the methyl group (−CH 3 ), a peak at 5.44 ppm for vinyl (−CH=CH−) protons, a peak at 2.13 ppm for (CH 2 –CH=CH−), and a peak at 2.76 ppm for CH 2 –NH 2 . In the 1 H NMR spectrum of KSFM@OAm, it is difficult to distinguish the NH 2 peak at approximately 1.13 ppm and CH 2 –CH 2 –NH 2 peak at approximately 1.37 ppm due to the broad methylene peak.…”
Section: Resultsmentioning
confidence: 99%
“…[14] In 2021, Han et al reported that KHF 2 :Mn 4+ water-soluble luminescent material could be used as a precursor to prepare Mn 4+ activated fluoride phosphors, successfully transferring Mn 4+ from pure water to K 2 SiF 6 host. [15] All the above synthesis methods can obtain particles within the micron size range, and the size distribution is not uniform, which is not suitable for MicroLED devices. More recently, Wang's research team developed a surfactant-free stepwise cation exchange synthesis in a non-HF system of cubic K 2 SiF 6 :Mn 4+ nano phosphor.…”
Section: Introductionmentioning
confidence: 99%